Dermoscopy of Actinic Lichen Planus in Skin of Color - Awatef Kelati; Asmae Rasso; Soumiya Chiheb (Mattioli1885, 2024)
Introduction: Actinic Lichen Planus (ALP) is a rare photosensitive variant of lichen planus. Four subtypes can be distinguished: pigmented, annular (AALP), plaque-like and dyschromic ALP. Methods: This is a retrospective; descriptive and analytical study investigating the dermoscopic patterns of different subtypes of ALP in skin of color. Results: Sixteen adult patients were included in this study; the majority of them were young females; while five patients with the pigmented subtype of ALP were more than 50 years old. This subtype was more prevalent in patients with phototype IV. AALP was described in men with a very dark phototype. In pigmented melasma-like ALP, dermoscopy showed an annular granular pattern, white reticular and circular  Wickham striae (WS) with hypopigmentation lacking skin creases, dots inside circles; and an eccentric pigmentation on circles. In  AALP, annular, circular WS; and perifollicular white halos with follicular plugs were described. The black hole pattern with dotted vessels was seen in the dyschromic ALP. White-yellow-bluish WS were noticed in plaque-type ALP with circumferential radial lines at the periphery.  Conclusions: This descriptive study of dermoscopic patterns of various subtypes of ALP in skin of color highlighted new dermoscopic descriptions that vary according to the clinical variant or the morphology; lesions distribution; and phototype. Also, many epidemiological differences were found between our results and the literature concerning the older age of onset in melasma-like pigmented ALP, and the male predominance in annular ALP.